Wakaf dan Kemandirian Pesantren dari Tebuireng Hingga Gontor - Miftahul Huda (Islamica: Jurnal Studi Keislaman, 2012)
This paper focuses on the notion of endowment and its role in the building and development of pesantren in Indonesia. It is interested particularly in investigating the economically independent nature of pesantren through the scheme of endowment. It also traces the history of pesantren to show that it has been independent all along. Its independence, the paper argues expands not only in economic terms but also in academic, theological as well as intellectual realm. Even against the onslaught of modernity, pesantren has been independent in the sense that it has not fallen prey to the negative impacts of modernity, if any. This paper discusses this as well as the strategy of pesantren in dealing with modernity particularly by referring to the experience of two great pesantrens, namely Tebuireng and Gontor. The paper keeps in mind that it is the values of the two pesantrens that kept them intact from the influence of modernity. It investigates therefore the nature and kind of these values as well the extent to which the two pesantrens are attached to them. One of the values that the paper is interested in is the notion of charity (sadaqah), the some-what equivalent word for endowment (waqf).